STEAM-Based E-LKPD to Enhance Learning Independence on States of Matter Topic - Yunita Miftahul Jannah; Ika Febriana Wati; Melania Eva Wulanningtyas (STEAM Journal For Elementary School Education, 2025)
This study aimed to develop an E-LKPD based on the STEAM approach on the topic of changes in the state of matter to improve the learning independence of fourth-grade elementary school students. The study employed the 4D development model (Define, Design, Develop, Disseminate). The subjects in this study were five fourth-grade students at SDN 1 Wonocoyo, Pogalan Sub-district, Trenggalek District. The instruments used included expert validation sheets, student response questionnaires, and learning independence questionnaires. The validation results showed that the E-LKPD was highly feasible for use, with an average validation score of 90%. Student responses to the E-LKPD indicated a high level of engagement and interest, reaching 92%. In addition, students’ learning independence scores increased significantly after using the E-LKPD, with a gain score of 0.47 (moderate category). Thus, the STEAM-based E-LKPD proved effective in enhancing the learning independence of fourth-grade students at SDN 1 Wonocoyo, Pogalan Sub-district, Trenggalek District.